2018
DOI: 10.1016/j.celrep.2018.02.047
|View full text |Cite
|
Sign up to set email alerts
|

ERRγ Promotes Angiogenesis, Mitochondrial Biogenesis, and Oxidative Remodeling in PGC1α/β-Deficient Muscle

Abstract: PGC1α is a pleiotropic co-factor that affects angiogenesis, mitochondrial biogenesis, and oxidative muscle remodeling via its association with multiple transcription factors, including the master oxidative nuclear receptor ERRγ. To decipher their epistatic relationship, we explored ERRγ gain of function in muscle-specific PGC1α/β double-knockout (PKO) mice. ERRγ-driven transcriptional reprogramming largely rescues muscle damage and improves muscle function in PKO mice, inducing mitochondrial biogenesis, antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 32 publications
5
42
0
Order By: Relevance
“…ERRγ interacts with PGC‐1α and plays a central role in regulating the mitochondrial energy metabolism 62 . Notably, ERRγ overexpression promotes angiogenesis and mitochondrial biogenesis independently of PGC‐1α, resulting in increased oxidative remodeling of muscle fibers and increased exercise performance 39 . In this study, we found increased mRNA and protein expression of ERRγ in the mouse gastrocnemius muscle.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…ERRγ interacts with PGC‐1α and plays a central role in regulating the mitochondrial energy metabolism 62 . Notably, ERRγ overexpression promotes angiogenesis and mitochondrial biogenesis independently of PGC‐1α, resulting in increased oxidative remodeling of muscle fibers and increased exercise performance 39 . In this study, we found increased mRNA and protein expression of ERRγ in the mouse gastrocnemius muscle.…”
Section: Discussionsupporting
confidence: 50%
“…UPLC‐QTOF‐MS/MS analysis showed that U pinnatifida extracts contained hesperetin and caffeic acid (Figure S3). Present study intended to show the potential effects of fucoxanthin, hesperetin, and caffeic acid present in U pinnatifida extracts on the regulation of master regulators for exercise adaptation and skeletal muscle function 39 . Fucoxanthin increased protein expression of phospho‐AMPK, PGC‐1α, ERRγ, ERRα, SIRT1, and NRF2 in C2C12 myotubes (Figure 7A).…”
Section: Resultsmentioning
confidence: 97%
“…Compared with IMAGE analysis in mTg mice ( S2 Table ), NFKB2, ZFP91, ATF4, and TBX15 were uniquely identified as causal factors in exercise. To verify motif predictions from our analyses, we compared genome-wide DNA binding sites of transgenically expressed Errg in Quad [40] to EMRs. Nearly 30% (778/2,662) of EMRs colocalized with ERRγ bound sites ( Fig 9F, left), in keeping with the strong enrichment of ERR/NR binding sites predicted in our motif analysis.…”
Section: Resultsmentioning
confidence: 99%
“…PGC1α also controls the expression of Vegf and other pro-angiogenic genes by recruiting estrogen-related receptor α (ERRα) to conserved binding sites within their promoters (49,50). In contrast to Errγ, loss of Pgc1α does not affect baseline muscle capillary density (43,51), but mice lacking Pgc1α or Errα in myofibers fail to increase vascular density in response to exercise (50,52). Even though PGC1α/ERRα control Vegf expression independently of hypoxia signaling via the hypoxia inducible factor (HIF) 1α (49), hypoxia increases PGC1α gene expression (49,53) and the Pgc1α-mediated increase in mitochondrial content can indirectly promote cellular hypoxia due to increased oxygen consumption (54).…”
Section: Exercise-induced Changes In Metabolism Of Skeletal Muscle Cementioning
confidence: 99%